Structure determination and tautomeric transition of 3-amino-1{[bis(benzylsulfanyl)methylidene]amino}urea - How, Fiona Ni Foong; Jamaluddin, N.; Abdul Halim, S. N.; Lee, V. S. (Pleiades Publishing, Ltd., 2015)
The single crystal X-ray analysis of 3-amino-1{[bis(benzylsulfanyl)methylidene]amino}urea shows that the compound crystallizes in the triclinic system with the space group P-1 and Z = 4. The asymmetric unit contains two independent molecules of 3-amino-1{[bis(benzylsulfanyl)methylidene]amino}urea. Both bis(benzylsulfanyl)methylidene groups are in a trans configuration with respect to the C16/O1/N3/N4 and C32/O2/N7/N8 fragments, respectively. The tautomeric transition energies of the three tautomeric forms are calculated at the generalized gradient approximation (GGA) level by the BLYP/DND method to estimate the kinetic and thermodynamic barriers. The keto form has a lower energy than the other two forms. Relatively lower values of kinetic barriers (about 58 kcal/mol for the transition between (a) and (b) forms) are found.